TURKISH INTERNATIONAL PRIVATE LAW: THE CASE OF RECOGNITION AND ENFORCEMENT OF FOREIGN JUDGMENTS - Liakopoulos, Dimitris (Revista da EMERJ, 2018)
The main purpose of this study is to present the conditions for the recognition and enforcement of foreign judgments in Turkey under Turkish law, with emphasis on judicial decisions and a more follows reference to arbitration decisions. Due to the breath of the subject for which extensive literature has been developed in Turkish science as well as important jurisprudence, it has been considered appropriate to limit the development of this study to the presentation of the provisions of current Turkish law through its sources, notably the Code of Private International and Procedural Law (MÖHUK), as well as the way in which it is interpreted and applied, both in theory and in case law.